Desert exploration in North Africa: some generalisations. (November 2019) - Goudie, Andrew
Abstract: This paper considers some of the general issues relating to the history of exploration in the Libyan (Western) Desert. These issues are: why there have been remarkably few books on desert exploration; the despised role of the motor car which was so important in the exploration of the Libyan Desert; the longevity of some explorers, the prominent role of women in Islamic travels; the great deal of time – sometimes years – that some of the explorers spent in the field; the role of indigenous people; the parts played by professionals, and amateurs; the undertaking of scientific work of high quality, not least in the field of geomorphology; and the international nature of exploration. Abstract : تتناول هذه الورقة بعض المواضيع العامة المتعلقة بتاريخ استكشاف الصحراء الليبية (الغربية). هذه المواضيع تشمل: لماذا يوجد عدد قليل جدا من الكتب حول استكشاف الصحراء، الدور الغير مرغوب فيه للسيارة و التي كانت مهمة جدا في استكشاف الصحراء الليبية، طول فترة خدمة بعض المستكشفين، الدور البارز للنساء في الأسفار الإسلامية ، القدر الكبير من الزمن – في بعض الأحيان سنوات – الذي أمضاه بعض المستكشفين في هذا المجال، دور السكان الأصليين، الدور الذي لعبه المحترفون والهواة، القيام بأعمال علمية ذات جودة عالية، ليس أقلها في مجال الجيومورفولوجيا (geomorphology)، والطبيعة الدولية للاستكشاف .